2013
DOI: 10.1158/1078-0432.ccr-12-3666
|View full text |Cite
|
Sign up to set email alerts
|

Cyclophosphamide Induces a Type I Interferon–Associated Sterile Inflammatory Response Signature in Cancer Patients' Blood Cells: Implications for Cancer Chemoimmunotherapy

Abstract: Purpose: Certain chemotherapeutics, particularly cyclophosphamide, can enhance the antitumor efficacy of immunotherapy. A better understanding of the cellular and molecular basis of cyclophosphamide-mediated immunomodulation is needed to improve the efficacy of chemoimmunotherapy. Experimental Design: Transcript profiling and flow cytometry were used to explore cyclophosphamide-induced immunoadjuvanticity in patients with hematologic malignancies. Results: A single high-dose treat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
64
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(72 citation statements)
references
References 49 publications
7
64
0
1
Order By: Relevance
“…In this case, the observed therapeutic effect resembled that noted following administration of autovaccine of in vitro irradiated leukaemic cells [33,37,47]. Also administration of dendritic cells was suggested as an anti-neoplastic vaccine [34,53], the effect of which might be amplified by low doses of chemotherapeutic drugs [59].…”
Section: Description Of Principles In Tumour Treatment Taking Into Asupporting
confidence: 57%
See 1 more Smart Citation
“…In this case, the observed therapeutic effect resembled that noted following administration of autovaccine of in vitro irradiated leukaemic cells [33,37,47]. Also administration of dendritic cells was suggested as an anti-neoplastic vaccine [34,53], the effect of which might be amplified by low doses of chemotherapeutic drugs [59].…”
Section: Description Of Principles In Tumour Treatment Taking Into Asupporting
confidence: 57%
“…However, another approach to the problem is possible: tumour cells, similarly to normal cells may die due to apoptosis. Administration to the patient of cells of his own antigens, in the form of extracts, tumour lysates, viable cells with induced apoptosis may provide autovaccine and it provides the patient with objective clinical responses more frequently (in 8.1% of the patients ) in various tumours than in patients following therapy employing individual tumour antigens (a response in 3.6% patients) [47]. Administration of autovaccine leads to presentation to lymphocytes T of the current tumour cell epitopes; current since a neoplastic tumour consists of various pathologically altered cells and the scope of their antigens alters during tumour development.…”
Section: Description Of Principles In Tumour Treatment Taking Into Amentioning
confidence: 99%
“…104 In patients with hematological malignancies, the administration of high-dose cyclophosphamide induced a rapid, transient and broad transcriptional modulation on peripheral blood mononuclear cells resulting in DNA damage, cell death and, noticeably, a Type-I-IFN signature. 106 This promoted the establishment of a systemic sterile inflammatory response characterized by the release of endogenous adjuvant signals able to enhance the efficacy of immunotherapy. 106 Similar to chemotherapy, radiation therapy was also reported to increase the levels of Type-I-IFNs and CXCL10 in the TME.…”
Section: The Role Of Type-i-ifns In Anticancer Therapymentioning
confidence: 99%
“…106 This promoted the establishment of a systemic sterile inflammatory response characterized by the release of endogenous adjuvant signals able to enhance the efficacy of immunotherapy. 106 Similar to chemotherapy, radiation therapy was also reported to increase the levels of Type-I-IFNs and CXCL10 in the TME. 107 In this study, CXCL10 was shown to promote tumor CD8 C T cell-homing and cytolytic activity.…”
Section: The Role Of Type-i-ifns In Anticancer Therapymentioning
confidence: 99%
“…We observed that infiltrated CD4 + T cells consistently expressed constantly higher levels of LAMP1/CD107a and additional inflammatory cytokines, particularly type I interferon [10,26,27]. CTX can enhance the expression of IL-2 [28] and type I interferon [29]. Thus, once CD4 + T Naito 15 cells entered into tumor sites, these cells differentiated into CD4 + CTLs under the influence of these cytokines.…”
Section: Direct Migration Of Ccirculating Cd4 + T Cells Directly Migrmentioning
confidence: 80%